2016
DOI: 10.5860/lrts.60n3.169
|View full text |Cite
|
Sign up to set email alerts
|

Literature of Acquisitions in Review, 2012–13

Abstract: The acquisitions literature published in 2012–13 shows a strong focus on nontraditional purchasing models, especially for electronic books (e-books). Patron Driven Acquisition (PDA) is one method that helps librarians cope with budget constraints that continue to plague library budgets. The expense of Big Deals has some libraries seeking more efficient alternatives such as Pay-Per-View or Evidence-Based Selection, however, many libraries are still reliant on the depth of coverage and perceived value of Big Dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…This has resulted in producing a large amount of research literature over the years. A review of literature on e-book acquisition 46 is an indication of the large quantity and variety of literature on e-book acquisition. The review specifically identified that the researchers have focused on non-traditional purchasing models including PDA and some libraries have preferred pay-per-view or evidence-based selection and some have even preferred the Big Deal model.…”
Section: E-books Collection Developmentmentioning
confidence: 99%
“…This has resulted in producing a large amount of research literature over the years. A review of literature on e-book acquisition 46 is an indication of the large quantity and variety of literature on e-book acquisition. The review specifically identified that the researchers have focused on non-traditional purchasing models including PDA and some libraries have preferred pay-per-view or evidence-based selection and some have even preferred the Big Deal model.…”
Section: E-books Collection Developmentmentioning
confidence: 99%